Periostin as a Biomarker for Nasal Polyps in Chronic Rhinosinusitis. (January 2018) - Maxfield, Alice Z.; Landegger, Lukas D.; Brook, Christopher D.; Lehmann, Ashton E.; Campbell, Adam P.; Bergmark, Regan W.; Stankovic, Konstantina M.; Metson, Ralph
Objective: Periostin is an extracellular matrix protein that is elevated in the sinonasal tissues of patients with chronic rhinosinusitis (CRS). The purpose of this study was to determine whether serum periostin could serve as a molecular biomarker of nasal polyp burden in sinonasal disease. Study Design: Prospective cohort study. Setting: Academic medical center. Subjects and Methods: Serum periostin levels were measured by ELISA on blood samples collected from patients undergoing sinus surgery for CRS (n = 71), further stratified by phenotype as defined by nasal polyps and asthma. Results were compared with assays performed on control subjects (n = 62). Results: Mean serum periostin levels were markedly elevated in patients with CRS versus controls (66.1 ng/mL [95% CI, 51.6-80.6] vs 38.7 ng/mL [95% CI, 34.4-42.9], respectively, P = .004). In addition, mean periostin levels were significantly higher in CRS patients with nasal polyps as compared with those without polyps (94.8 ng/mL [95% CI, 67.3-122.4] vs 41.1 ng/mL [95% CI, 35.2-47.0], respectively, P < .001). Periostin levels did not correlate with sex ( P = .473), smoking history ( P = .748), aspirin-exacerbated respiratory disease status ( P = .136), oral steroid use within 1 month of surgery ( P = .281), use of topical steroid nasal spray ( P = .864), or number of prior sinus operations ( P = .973). Conclusion: Serum periostin appears to be a novel molecular biomarker for the presence of nasal polyps and may serve as an indicator of CRS endotypes.